Binary Microcrystal Additives Enabled Antisolvent‐Free Perovskite Solar Cells with High Efficiency and Stability. Issue 7 (28th December 2022) - Wang, Deng; Chen, Jiabang; Zhu, Peide; Qiao, Ying; Hu, Hang; Zeng, Jie; Zhang, Jiyao; Qu, Geping; Wang, Yanggang; Wang, Xingzhu; Jen, Alex K.‐Y.; Xu, Baomin
Abstract: Developing a facile method to prepare high‐quality perovskite films without using the antisolvent technique is critical for upscaling production of perovskite solar cells (PVSCs). However, the as‐prepared formamidinium (FA)‐based perovskite films often exhibit poor film quality with high density of defects if antisolvent is not used, limiting the photovoltaic performance and long‐term stability of derived PVSCs. Herein, this work adopts pre‐synthesized 3D methylammonium lead chloride (MAPbCl3 ) and 1D 2‐aminobenzothiazole lead iodide (ABTPbI3 ) microcrystals into self‐drying perovskite precursors, which serve as seed crystals to promote nucleation and growth of FAPbI3 ‐based perovskites without requiring antisolvent extraction. The combined binary microcrystals facilitate the formation of a dense and pinhole‐free perovskite film with a stable perovskite lattice and defect‐healed grain boundaries, enabling efficient charge carrier transfer and reduced non‐radiative recombination loss. As a result, the best‐performing inverted architecture device exhibits a champion power conversion efficiency of 23.27% for small‐area devices (0.09 cm 2 ) and 21.52% for large‐area devices (1.0 cm 2 ). These values are among the highest efficiencies reported for antisolvent‐free PVSCs. Additionally, the unencapsulated device shows enhanced moisture, thermal, and operational stabilities, and maintains 92% of its initial efficiency after being held at the maximum power point for 1000 h. Abstract : By employing pre‐synthesized 3D methylammonium lead chloride (MAPbCl3 ) and 1D 2‐aminobenzothiazole lead iodide (ABTPbI3 ) microcrystals into a self‐drying perovskite precursor, this work successfully modifies the crystallization process without antisolvents and reduces defects at grain boundaries. Furthermore, the best‐performing inverted device exhibits a champion power conversion efficiency of 23.27% for small‐area devices (0.09 cm 2 ) and 21.52% for large‐area devices (1.0 cm 2 ).